2018
DOI: 10.5812/semj.60497
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and Evaluation of Program Performance and Management Control System of Tuberculosis: A Ten-Year Cross-Sectional Study in Sistan and Baluchestan Province, Iran

Abstract: The aim of this study was to monitor and evaluate the program performance and management control system of tuberculosis in Sistan and Baluchestan Province by comparing the annual indicators over ten years. This descriptive study was performed in the health departments of the province, using the records of tuberculosis patients during 2006 -2016. Data were analyzed in SPSS version 23. The lowest rate of smear-positive pulmonary tuberculosis was reported in 2011 (27.23%). Based on the findings, the incidence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…The Family Health Strategy is the preferred gateway for users to treat the disease, where embracement is carried out through comprehensive assistance providing the link between user and health professional. Studies have found that difficulties in accessing US can delay diagnosis and reduce the success of treating the disease 20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…The Family Health Strategy is the preferred gateway for users to treat the disease, where embracement is carried out through comprehensive assistance providing the link between user and health professional. Studies have found that difficulties in accessing US can delay diagnosis and reduce the success of treating the disease 20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…There was also no relationship between increasing or decreasing age and smear grading. In other studies, children under 15 years old were in the study group and therefore due to differences in the study population it is not possible to compare the results [4][5][6] . Most patients were from Zabol city (52.5%) and the least were from Hamoon and Helmand cities (2%).…”
Section: Discussionmentioning
confidence: 99%
“…The reduced TB prevalence in Iran is the result of the efforts made by the Ministry of Health and Medical Education (MoHME) in some major sectors, including the initiation of the BCG vaccination programme, the development of a national TB programme, implementing the DOTS strategy in 1997 and implementing a TB control programme in prisons [12]. Despite the decreasing trend of mortality due to TB in 2006-2016 [13], the incidence of TB is reported 14 per 100 000 in Iran [14], and Sistan and Baluchestan Province and Golestan Province still have the highest number of people with TB [15,16]. Neighbouring countries Pakistan, Afghanistan and Iraq, which have the highest numbers of TB cases [17], and poverty, which is a challenge to the control of this disease [18,19], have made the Sistan region of Sistan and Baluchestan Province a centre of TB in Iran in recent years 4.…”
Section: Introductionmentioning
confidence: 99%